The Lexicographical Description of the Stylistic and Lexical Properties of English Fixed Expressions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article discusses the specifics of the phraseology in English, the factors of formation, and the relation to literary language norms. It aims to interpret specification of simple verbal phrases, their formation reasons and their relationship to literary language norms. In article is also analyzed the theories of phraseology, using them in practical examples of everyday usage.